DC Link Voltage Control of Enhanced Bidirectional Z Source Inverter with Improved ADＲC - YAN Jing-bin; PIAO Jing-lin; LI Guan-da; ZHOU Chang; LIU Qing-lan (Journal of Harbin University of Science and Technology)
An improved auto disturbance rejection control technique ( ADＲC) is proposed to control the DC link voltage of the enhanced bidirectional Z source inverter. Firstly，the basic working principle of the enhanced bidirectional Z-source inverter is introduced，and the small-signal modeling of the enhanced bidirectional Z-source inverter indicates that the transfer function of the straight-through duty ratio to the Z-source network capacitor voltage contains the right half-plane. Zero，there is a non-minimum phase characteristic. In order to eliminate the non-minimum phase characteristics，the transient process is short，no overshoot，independent of the mathematical model of the ADＲC controller，indirectly controlling the DC link voltage by controlling the capacitor voltage; and the nonlinearity commonly used in the ADＲC controller Based on the function fal function，an improved lfal function is proposed to avoid high-frequency chattering and to accelerate the system gain reduction rate under large error conditions. The simulation analysis proves that the improved ADＲC is effective in the DC link voltage control of the enhanced bidirectional Z-source inverter and has stronger robustness